Impact of vascular thromboxane prostanoid receptor activation on hemostasis, thrombosis, oxidative stress, and inflammation. (February 2014) - Capra, V.; Bäck, M.; Angiolillo, D. J.; Cattaneo, M.; Sakariassen, K. S.
Summary The activation of thromboxane prostanoid (TP) receptor on platelets, monocytes/macrophages, endothelial cells, and vascular smooth muscle cells (SMC) plays important roles in regulating platelet activation and vascular tone and in the pathogenesis of thrombosis and vascular inflammation. Oxidative stress and vascular inflammation increase the formation of TP receptor agonists, which promote initiation and progression of atherogenesis and thrombosis. Furthermore, TP receptor activation promotes angiogenesis and vessel wall constriction. Besides thromboxane A2 and its endoperoxide precursors, prostaglandin G2 and H2, isoprostanes, and 20‐hydroxyeicosatetraenoic acid also activate TP receptor as autocrine or paracrine ligands. These additional TP activators play a role in pathological conditions such as diabetes, obesity, and hypertension, and their biosynthesis is not inhibited by aspirin, at variance with that of thromboxane A2. The understanding of TP receptor function increased our current knowledge of the pathogenesis of atherosclerosis and thrombosis, highlighting the great impact that this receptor has in cardiovascular disorders.